Time Varying Reliability Analysis of the MG 400/951 Shearer Cutting Part Planet Carrier - Minghao Li; Jie Qiao; Lijuan Zhao; Jiayi Fan; Meichen Zhang; Bing Luo (Jixie chuandong)
The cutting part planet carrier is the key part of the shearer，and its time-varying reliability has an important influence on the comprehensive performance of shearer. Rigid-flexible coupling model of shearer with planetary carrier as modal neutral file is established based on Pro/E，and weak areas and dynamic stress of the cutting part planet carrier are obtained by studying the dynamics performance of the planetary carrier. The probability density function of the three-parameter Weibull distribution in the weak region of the cutting part's planet carrier is obtained by Matlab and the rationality of its fitting is verified with Kstest function. According to the fatigue life reliability theory，the fatigue life reliability model of planetary carrier is established. By calculation，the time-varying reliability of multiple weak areas of planetary carrier based on Copula function is to degrade exponentially from 0.936 2 until the failure of the planetary carrier. Combined with reliability sensitivity design theory，the influence of multiple weak areas design variables on the time-varying reliability of the cutting part planet carrier is analyzed. This provides theoretical basis and accurate data support for related research on the planet carrier.